Effects of light intensity and LED spectrum on the medicinal component accumulation of hydroponic Hypericum perforatum L. under controlled environments - Gao, Wei; He, Dongxian; Zheng, Jianfeng; Li, Yan (International Journal of Agricultural and Biological Engineering, 2022)
Medicinal components of Hypericum perforatum L. plants varies widely due to fluctuations in growth environment and biotic and abiotic contamination during cultivation management. The quality of extracts or preparations is difficult to control because of the unstable raw materials. The aim of this study is to enhance the yield and medicinal component contents of H. perforatum by optimizing lighting factors under controlled environment. H. perforatum plants were hydroponically cultivated for 30 d under 3 levels of photosynthetic photon flux density (PPFD) with 200, 300, and 400 μmol/(m2·s) using white LEDs (R:B ratio is the ratio of red light to blue light, R:B ratio of 0.9 and 1.8) and white plus red LED (R:B ratio of 2.7). The results showed that PPFD and LED spectrum had significant effects on the growth and accumulation of medicinal components of H. perforatum. Biomass accumulation of stem, leaf, and root increased linearly with the increase of PPFD under each LED spectrum. Fresh weights and dry weights of stem, leaf, and root were significantly higher under a PPFD of 400 μmol/(m2·s) with R:B ratio of 0.9 than those of 200 μmol/(m2·s), respectively. The relative growth rate and net photosynthetic rate showed linear relationships with PPFD under the same LED spectrum. Total hypericin content, total hyperforin content, and energy yield of hypericin increased with increasing PPFD. Total hypericin content and energy yield of hypericin of P400-L0.9 were 78% and 89% more than those of P400-L2.7, respectively. Total hyperforin content and energy yield of hyperforin of P400-L0.9 and P400-L2.7 were no significant differences. Based on energy efficiency, an R:B ratio of 0.9 of white LEDs with a PPFD of 400 μmol/(m2·s) was beneficial to improve medicinal component contents of hydroponic H. perforatum in plant factory with LED lighting. Keywords: LED spectrum, light intensity, controlled environments, Hypericum perforatum L. DOI: 10.25165/j.ijabe.20221505.7373 Citation: Gao W, He D X, Zheng J F, Li Y. Effects of light intensity and LED spectrum on the medicinal component accumulation of hydroponic Hypericum perforatum L. under controlled environments. Int J Agric & Biol Eng, 2022; 15(5): 63–69.